Conductivity fluctuations of polycrystalline Ag-doped YBa2Cu3O7-δ superconductor - Azambuja,Paula de (2010)
Systematic conductivity measurements near T C in granular Ag-doped YBa2Cu3O7-δ superconductors are presented. Silver doped YBa2Cu3O7-δ samples were produced by different routes and characterized by X-ray diffraction, dc magnetization and electrical resistivity. The results were analyzed in terms of the temperature derivative of the resistivity and of the logarithmic temperature derivative of the conductivity, that allowed identifying power-law divergences in the conductivity. The results show that the resistive transition proceeds in two stages. In the normal phase, Gaussian and critical fluctuation conductivity regimes were identified. Close to the zero-resistance temperature, a coherence transition related to the connective nature of the granular samples was evidenced. It was not observed significant differences in critical and Gaussian fluctuations between pure and Ag-doped YBa2Cu3O7-δ polycrystalline samples.